Second Five-Year Plan of Orissa Districtwise Break-Up - Planning Commission (Planning Commission, 1957)
In the case of the schemes which are amenable to district-wise breakup but for which such breakup is available in part only that part provision is shown in the respective district-wise statements, the balance being shown in statement “A—General Schemes”. The minus provision shown in statement ‘A' for such schemes indicated the amounts for which district breakup has been prepared.
Government of Orissa Political and Services (Planning) Department
Government of Orissa Political and Services (Planning) Department